2016
DOI: 10.1007/s12192-016-0676-6
|View full text |Cite
|
Sign up to set email alerts
|

The human HSP70 family of chaperones: where do we stand?

Abstract: The 70-kDa heat shock protein (HSP70) family of molecular chaperones represents one of the most ubiquitous classes of chaperones and is highly conserved in all organisms. Members of the HSP70 family control all aspects of cellular proteostasis such as nascent protein chain folding, protein import into organelles, recovering of proteins from aggregation, and assembly of multi-protein complexes. These chaperones augment organismal survival and longevity in the face of proteotoxic stress by enhancing cell viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
429
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(450 citation statements)
references
References 314 publications
(373 reference statements)
4
429
0
17
Order By: Relevance
“…It is possible that HSP70 affects either Smad-dependent pathway or Smad-independent pathway of TGF-β signaling depending upon the cell species. On the other hand, it is well known that HSP70, conjuncted with the E3 ubiquitin ligase C-terminal Hsp70-interacting protein, promotes the ubiquitination and subsequent proteasomal degradation [10, 42]. It has been shown that the induction of HSP70 inhibits the TGF-β signaling through its direct binding to TGF-β type I receptor, resulting in the ubiquitination and degradation of the complex in embryonic kidney cells [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that HSP70 affects either Smad-dependent pathway or Smad-independent pathway of TGF-β signaling depending upon the cell species. On the other hand, it is well known that HSP70, conjuncted with the E3 ubiquitin ligase C-terminal Hsp70-interacting protein, promotes the ubiquitination and subsequent proteasomal degradation [10, 42]. It has been shown that the induction of HSP70 inhibits the TGF-β signaling through its direct binding to TGF-β type I receptor, resulting in the ubiquitination and degradation of the complex in embryonic kidney cells [43].…”
Section: Discussionmentioning
confidence: 99%
“…The HSP family have been recently classified into seven groups including HSPA (HSP70), HSPC (HSP90) and HSPH (HSP110) [6]. Among the members of HSPs, HSP70 (HSPA) ubiquitously exists in unstressed cells and functions as an ATP-dependent molecular chaperone for the assistance of folding newly synthesized proteins, and the translocation of proteins into the different cellular compartments [7-10]. Accumulating evidence indicates potent effects of HSP70 toward various diseases, such as cancer, infection and autoimmune diseases [4, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular HSP70s carry out immunomodulatory functions as cross-presenters of immunogenic peptides via the major histocompatibility complex (MHC) found on the surfaces of cells (in all higher vertebrates), helping the immune system to recognize foreign substances. In humans a MHC complex is also called the human leukocyte antigen (HLA) and functions as a chaperokine which stimulates innate and adaptive immunity as well as stimulating the innate immune responses mediated by natural killer (NK) cells (see review of [24]). Note also that the "immunoglobulin heavy-binding protein" or Grp78 or BiP is located in the lumen of the ER.…”
Section: The Hsp 70 Familymentioning
confidence: 99%
“…The HSP70 family contains stress-inducible members (HSPA1) and constitutively expressed members (HSPA8) [23]. We found that polyI:C stimulation induced HSPA1 mRNA but not HSPA8 mRNA (Fig.…”
Section: Hsp70 Is Induced By Dsrna Stimulation and Inhibits The Mda5-mentioning
confidence: 83%
“…HSP40s (also referred to as J proteins) work as cofactors of HSP70s that are involved in various biological processes, such as protein refolding, protein interaction, and protein transport, by supporting protein conformational changes in an ATP-dependent manner [23]. DNAJB1 thus may interfere with MDA5 oligomerization by coupling with HSP70.…”
Section: Introductionmentioning
confidence: 99%